Multisystem T-cell Chronic Active Epstein-Barr Virus Infection: From the Eye to the Kidney. (18th August 2022) - Vial, Guillaume; Barthod, Laure; Schneider, Sophie; Mercié, Patrick; Duffau, Pierre; Vermorel, Agathe; Ribeiro, Emmanuel
Abstract: Chronic active Epstein-Barr virus (CAEBV) infection is usually a fatal disease associated with clonal proliferation of EBV-infected T or NK cells. We present the case of a 33-year-old Peruvian patient who developed a multisystem CAEBV, notably responsible for exceptional ophthalmological and renal damage. We describe the clinicopathological features of EBV-induced lymphoproliferative disorder.